How ‘reciprocal tariffs’ harm agricultural trade - Glauber, Joseph W.; Piñeiro, Valeria; Gianatiempo, Juan Pablo (International Food Policy Research Institute, 2025)
Citing the persistent U.S. trade deficit and what he considers unfair practices by other countries, President Donald Trump declared April 2 “Liberation Day” and announced a sweeping new set of supplemental tariffs on imports from nearly all major U.S. trading partners. This announcement follows a series of previous actions taken since the beginning of the administration, including 20% tariffs on Chinese imports, 25% tariffs on automobiles and auto parts, and duties on steel and aluminum.